Penyebab Adam dan Hawa Turun dari Surga dalam Alquran dan Bible dalam Persperktif Feminisme Muslim: Sebuah Telaah Ulang - Moh. Syafi’ (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
This paper to prove whether the story of Adam and Eve fell from heaven in the text of the Koran and the Bible are "the gender Refraction " or not, that is the study in this paper. To prove that there are jender refraction or not in this text the author describe similarities and differences in the story, and then analyzed through comparative analysis, in order to prove the presence and absence of Muslim feminist assumptions about unclear gender of the story in the Bible. From the comparative analysis of the two texts not found gender refraction that is the women as the cause of falling of Adam and Eve from paradise. In the Qur'an mentioned the cause is Satan while in the Bible is a snake, even though the Bible contains many stories israili cargo that is not credible.